Absence of active systemic anaphylaxis in guinea pigs upon intramuscular injection of inactivated SARS-CoV-2 vaccine (Vero cells). (3rd September 2022) - Huang, Zhangqiong; Li, Yun; Yi, Hongkun; Wu, Zhengcun; Li, Cong; Du, Tingfu; Yang, Jinling; Wang, Yixuan; Jiang, Qinfang; Fan, Shengtao; Liao, Yun; Zhang, Ying; et al.
Abstract: Background: The safety of novel vaccines against COVID-19 is currently a major focus of preclinical research. As a part of the safety evaluation testing package, 24 healthy guinea pigs were used to determine whether repeated administration of inactivated SARS-CoV-2 vaccine could induce active systemic anaphylaxis (ASA), and to evaluate its degree of severity. Method: According to sex and body weight, the animals were randomly divided into three experimental groups (eight animals per group). The negative control group received 0.9% sodium chloride (priming dose: 0.5 mL/animal; challenge dose: 1 mL/animal); the positive control group received 10% ovalbumin (priming dose: 0.5 mL/animal; challenge dose: 1 mL/animal); and the inactivated SARS-CoV-2 vaccine group received inactivated SARS-CoV-2 vaccines (priming dose: 100 U in 0.5 mL/animal; challenge dose: 200 U in 1 mL/animal). Priming dose administration was conducted by multi-point injection into the muscles of the hind limbs, three times, once every other day. On days 14 and 21 after the final priming injection, a challenge test was conducted. Half of the animals in each group were injected intravenously with twice the dose and volume of the tested substance used for immunization. During the experimental course, the injection site, general clinical symptoms, body weight, and systemic allergic reaction symptoms were monitored. Result: After intramuscular injection of inactivated SARS-CoV-2 vaccine, there were no abnormal reactions at the injection site, clinical symptoms, or deaths. There was no difference in body weight between the groups, and there were no allergic reactions. Conclusion: Thus, inactivated SARS-CoV-2 vaccine injected intramuscularly in guinea pigs did not produce ASA and had a good safety profile, which can provide actual data on vaccine risks and important reference data for clinical research on this vaccine.